Innovative Approaches in Environmental Engineering: Advanced Pollution Control Techniques and Sustainable Solutions - Mohsin, Abdullah Hayder Mohammed Ali; Khalaf, Fadi Hatem Hussein; Nasser, Abdulraqeb waleed hamad; Mahmoud, Mustafa mukhtar Mohammed (American Journal of Botany and Bioengineering, 2025)
The rapid industrialization and population growth have intensified environmental pollution, creating challenges in air, water, and soil quality management. Despite advancements in pollution control, there remains a gap in integrating sustainable and innovative solutions for effective environmental remediation. This study reviews advanced pollution control techniques, including bioelectrochemical systems, bioremediation, and nanotechnology-based approaches, to address contemporary environmental issues. Findings indicate that these emerging technologies offer improved pollutant removal efficiency, energy recovery potential, and reduced environmental impact. The results underscore the importance of integrating green technologies and sustainable engineering solutions to mitigate pollution and promote a cleaner, healthier environment. Future research should focus on optimizing these technologies for large-scale applications to achieve long-term sustainability.